Dietary patterns and cardiometabolic diseases in 0.5 million Chinese adults: a 10-year cohort study - Qin, C; Lv, J; Yu, C; Guo, Y; Bian, Z; Gao, M; Du, H; Yang, L; Chen, Y; Shen, L; Zhou, S; Chen, J; et al. (BioMed Central, 2021)
Background The effect of the overall diet quality on cardiometabolic diseases has been well studied in the Western population. However, evidence is still in need regarding dietary patterns depicting unique Chinese dietary habits and their associations with cardiometabolic diseases.